An Interpretative Phenomenological Analysis of the use of psilocybin by veterans with symptoms of trauma. (September 2022) - Smith, FL; Neill, JC; Wainwright, V
Veterans are at increased risk of experiencing symptoms of trauma. Although many benefit from available treatments, some find treatment inaccessible or ineffective and explore alternative substances. One such substance is psilocybin. This Interpretative Phenomenological Analysis study aimed to provide an initial insight into the experiences of veterans who have used or have considered using psilocybin and their perspectives regarding the acceptability of it as a treatment for their self-reported symptoms of trauma. Seven veterans with current or historic trauma symptoms were interviewed. All participants had either used or considered using psilocybin to alleviate their symptoms. All participants reported perceiving barriers when accessing treatment with many considering psilocybin out of desperation. All participants who had used psilocybin reported immediate and long-term improvements in their symptomatology. The study suggests that some perceive current treatments as ineffective and/or inaccessible, leading to the consideration of alternatives, such as psilocybin. The immediate and long-term symptom reductions reported suggest it may be a viable treatment option for symptoms of trauma for some. However, further research and clinical trials are required to form conclusions on the therapeutic potential of psilocybin for this group.